Analisis Perilaku Konsumen dalam Pembelian Produk Sayuran di Toko Alfresh - Astiani, Ajeng Dwi; Robbani, Hamzah; Alianny, Alin (LITERATUS, 2023)
This research is to determine consumer behavior in purchasing vegetable products at the Alfresh Store. This research was conducted using a qualitative descriptive method. The data sources used are primary data and secondary data which help complete the research data, with data collection techniques through interviews. The results of this research show that consumer behavior patterns are in accordance with the approach (Awareness, Appeal, Ask, Act, Advocate) Hermawan Kertajaya is Effective. Without realizing it, consumers have actually implemented an approach in accordance with Hermawan Kertajaya's 5A. Awareness consumers know Alfresh from their neighbors, Appeal is what makes consumers interested in Alfresh because it is attractive in terms of place and logo. Ask asks about the price and quality of the product. Act finally made a purchase at Alfresh because of the service and product quality at Alfresh. The consumer advocate recommended Alfresh to his neighbors